Use of Guanfacine for Cannabis Use Disorder and Related Symptomology. Issue 6 (4th September 2019) - Holst, Manuela; Mathai, David S.; Patel, Marguerite M.; Rodgman, Christopher; Keller, Jake; Hussain, Mariyah Z.; De La Garza, Richard; Kosten, Thomas R.; Verrico, Christopher D.
Abstract : Background and Objectives: No medication has Food and Drug Administration approval for cannabis use disorder (CUD), and most medication development focuses on the withdrawal syndrome. We evaluated the effects of short‐term treatment using the α‐2A‐adrenergic receptor agonist, guanfacine, on withdrawal symptoms in volunteers with CUD and a history of early onset of cannabis use. Methods: Non‐treatment‐seeking healthy volunteers ( n = 7) who met the Diagnostic and Statistical Manual of Mental Disorders, 4th Edition criteria for CUD participated in a two‐phase, within‐subjects study. Volunteers received placebo or guanfacine (3 mg/day) for the first 8‐day inpatient study and the alternative medication for the second 8‐day inpatient study. On day 1 of both treatment periods, participants received 30 mg of synthetic Δ 9 ‐tetrahydrocannabinol for standardization of abstinence onset. On days 2 to 7, participants received study medication. Cannabis withdrawal symptoms, sleep, craving, and physiology were assessed on all inpatient days. Results: Compared with placebo, guanfacine did not show significant effects on withdrawal, craving, or sleep, although there were trends for guanfacine to increase positive mood symptoms and decrease craving‐associated compulsivity. Discussion and Conclusions: Compared with former studies, we could not prove significant improvement in sleep or decrease of negative symptoms, but we found trends for increased positive mood symptoms. Our data did not show significant effects of guanfacine on withdrawal symptoms or craving. Due to early and longer cannabis use, our subjects indicate a great severity of illness increasing the likelihood of treatment resistance. Scientific Significance: On the basis of trends demonstrated here and other lines of evidence, further investigation is warranted regarding the utility of guanfacine as a potential treatment for CUD. (Am J Addict 2019;00:1–10)